Quantification of Volumetric Bone Mineral Density of Proximal Femurs Using a Two-Compartment Model and Computed Tomography Images. (27th February 2018) - Liu, Yan-Lin; Hsu, Jui-Ting; Shih, Tian-Yu; Luzhbin, Dmytro; Tu, Chun-Yuan; Wu, Jay
Abstract : Objectives . Dual-energy X-ray absorptiometry (DXA) is frequently used to measure the areal bone mineral density (aBMD) in clinical practice. However, DXA measurements are affected by the bone thickness and the body size and are unable to indicate nonosseous areas within the trabecular bone. This study aims to quantify the volumetric bone mineral density (vBMD) using computed tomography (CT) images and the two-compartment model (TCM) methods. Methods . The TCM method was proposed and validated by dipotassium phosphate (K2 HPO4 ) phantoms and a standard forearm phantom. 28 cases with DXA scans and pelvic CT scans acquired within six months were retrospectively collected. The vBMD calculated by TCM was compared with the aBMD obtained from DXA. Results . For the K2 HPO4 phantoms with vBMD ranging from 0.135 to 0.467 g/cm 3, the average difference between the real and calculated vBMD was 0.009 g/cm 3 and the maximum difference was 0.019 g/cm 3 . For the standard forearm phantom with vBMD of 0.194, 0.103, and 0.054 g/cm 3, the average differences between the real and calculated vBMD were 0.017, 0.014, and 0.011 g/cm 3 . In the clinical CT image validation, a good linear relationship between vBMD and aBMD was observed with the Pearson correlation coefficient of 0.920 (p < 0.01 ). Conclusions . The proposed TCM method in combination with the homemade cortical bone equivalent phantom provides accurate quantification and spatial distribution of bone mineral content.